Interjection in Novel Resign by Almira Bastari - Prishandani, Arini; Nurainun; Mulyadi (TALENTA, 2024)
The background of this research was the discovery of interjection forms in the novel Resign by Almira Bastari. The aimed to obtain a description of the form of interjection and the type of interjection in the novel Resign by Almira Bastari. The data source used for this research was the novel Resign by Almira Bastari. The object of this research was written data as the main data studied, which relates to the form of the interject. The research data was in the form of phrases. The method of this research was using descriptive qualitative method with the method of data collection technique used was the listen method. The results of this study were the form of interjection which is divided into two parts, namely 1) primary interjection consisting of the exclamations oh, wah, nah, eh, ah, wow, hmm, yah, hah, lho, 2) secondary interjection consisting of interjections astaga, gila, damn, anjrit, aduh, alhamdulliah, anjing, ya ampun, yaelah, halah, damn, widih. The types of interjections found in Resign's novels were, among others, 1) the interjection of annoyance such as anjing, anjrit, sial, damn, gila; 2) admiration, namely widih; 3) gratitude like alhamdulilla; 4) hope like yah; 5) then wonder like aduh, eh, ah, oh ; 6) shock like astaga, wah, wow, hah, lho; 7) call like eh; 8) the conclusion was nah, hmm, yaelah, halah.